a) f(g(x)) = 2(6x-8/2-x)+8 / (6x-8/2-x)+6 = 12x-16+16-8x / 6x-8+12-6x = 4x/4 = x

b) g(f(x)) = 6(2x+8/x+6)-8 / 2-(2x+8/x+6) = 12x+48-8x-48 / 2x+12-2x-8 = 4x/4 = x

c) Since f(g(x)) = g(f(x)) = x the functions ARE inverses of each other.

For a and B can you also tell me what the x cant equals are. Thanks!

a) x can't equal 2

b) x can't equal -6

-----------------------------------------------------------------------------------

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up